NaSH increases SIRT1 activity and autophagy flux through sulfhydration to protect SH-SY5Y cells induced by MPP +. Issue 17 (1st September 2020) - Li, Jing; Li, Mei; Wang, Cui; Zhang, Shuhu; Gao, Qiang; Wang, Liping; Ma, Lan
ABSTRACT: Parkinson's disease (PD) is one of the most prevailing aging diseases around the world. The present study was to investigate the potential effect of hydrogen sulfide (H2 S) and silent mating type information regulation 2 homolog 1 (SIRT1) in MPP + induced SH-SY5Y cells and its underlying mechanisms in PD. SH-SY5Y cells were induced by MPP + and treated with the H2 S donor NaHS to detect the effect of H2 S on the molecular behaviors of MPP + induced SH-SY5Y cells. NaHS reduced the apoptosis rate and expressions of MDA, 4-HNE and p62, while increased cell viability, autophagy flux and expressions of LC3 II/I and Beclin1 in MPP + induced SH-SY5Y cells. Then, levels of autophagy-related proteins and inflammation-related proteins (TNF-α, IL-Iβ) were detected, indicating that Chloroquine and Sirtinol reversed the protective effect of H2 S on SH-SY5Y cells induced by MPP +. We further explored the particular function of H2 S, SH-SY5Y cells treated with MPP +, NaHS chloroquine, and SIRT1 inhibitor (Sirtinol). The results showed that H2 S increased SIRT1 expression and sulfhydration. Finally, a PD mouse model verified the above results. In a word, H2 S ameliorated SIRT1 activity through acceleration of SIRT1 sulfhydration to increase the autophagy flux and attenuate damage of SH-SY5Y cells induced by MPP +. H2 S and SIRT1 activator might be a target in the treatment of PD patients.